SINTESIS NANOPARTIKEL PERAK MENGGUNAKAN EKSTRAK KULIT BAWANG MERAH (Allium cepa L.) DAN UJI AKTIVITAS ANTIBAKTERI TERHADAP BAKTERI Staphylococcus aureus - Triyani Sumaiti; Devi Ratnasari; Dinda Dwi Mutiani (Sekolah Tinggi Teknologi Industri dan Farmasi Bogor, 2018)
Synthesis of silver nanoparticle and determination of its antibacteial activity for Staphylococcus aureus were studied in this research. Silver nanoparticle (NPAg) were synthesized using method green synthesisby reacting extract peel of onion (Allium cepaL.) and silver nitrate (AgNO3). NPAg synthesis used variation AgNO3 0,1mM (F1); 0,5mM (F2) and 1,0mM (F3). Characterization using UV-Visible spektroscopy and Particle Size Analyzer (PSA). UV-Visible spektroscopy analysis showed that the NPAg at F2 and F3 in 400-500 nm wavelenght. The particle size used PSA at F1, F2 and F3 in 390,7 nm, 62,34 nm and 50,63 nm. F3 has been tested for antibacteial activity S.aureus, the result showed that the antibacterial activity at F3 much better than AgNO3 1,0 mM which is not nanometer scale.